Fosfito de potássio não protege plantas de milho contra os efeitos fitotóxicos do glyphosate1 - Gomes, Giovanna Larissa Gimenes Cotrick [UNESP]; Velini, Edivaldo Domingues [UNESP]; Carbonari, Caio Antonio [UNESP] (Escola de Agronomia e Engenharia de Alimentos/UFG, 2015)
There are conflicting reports on the effect of potassium phosphite with or without glyphosate in plants. Some of them indicate that potassium phosphite may cause injuries when applied alone, while others point out that it can reduce the injury caused by glyphosate, when applied in association with this herbicide. This study aimed at evaluating the effect of potassium phosphite alone or in association with glyphosate on visual injury, dry matter accumulation, phytotoxicity indicator compounds levels and aromatic amino acid contents in maize plants. Treatments consisted of isolated or associated application of two glyphosate doses (72 g ha-1 and 720 g ha-1) and one potassium phosphite dose (Fosway - 3 L ha-1). The visual evaluations of injury and harvesting were performed at 2, 4, 10 and 15 days after application. The potassium phosphite applied alone did not cause injury to plants, and its association with glyphosate, regardless of the dose tested, did not protect the plants against the injury and dry mass reduction caused by the herbicide. There was an accumulation of shikimic and quinic acids on the plants subjected to the highest dose of glyphosate with or without phosphite. The potassium phosphite treatments with or without glyphosate showed higher tryptophan levels and did not alter the phenylalanine and tyrosine contents in the plants.

Existem relatos controversos sobre o efeito do fosfito de potássio, associado ou não ao glyphosate, em plantas. Alguns indicam que o fosfito de potássio pode causar injúrias, quando aplicado isoladamente, enquanto outros destacam que ele pode reduzir a injúria causada pelo glyphosate, quando aplicado em conjunto com este herbicida. Este estudo objetivou avaliar o efeito do fosfito de potássio, em associação ou não com o glyphosate, sobre a injúria visual, acúmulo de massa seca, níveis de compostos indicadores de fitotoxicidade e teores de aminoácidos aromáticos, em plantas de milho. Os tratamentos consistiram na aplicação isolada ou em associação de duas doses de glyphosate (72 g ha-1 e 720 g ha-1) e uma de fosfito de potássio (Fosway - 3L ha-1). As avaliações visuais de injúria e coletas de material vegetal foram realizadas aos 2, 4, 10 e 15 dias após a aplicação. O fosfito de potássio aplicado isoladamente não ocasionou injúrias às plantas e a sua associação com o glyphosate, independentemente da dose testada, não protegeu as plantas contra a injúria e a redução de massa seca causada pelo herbicida. Houve acúmulo dos ácidos chiquímico e quínico nas plantas submetidas à maior dose de glyphosate associada ou não ao fosfito. O fosfito de potássio, associado ou não ao glyphosate, promoveu maiores teores de triptofano e não alterou os teores de fenilalanina e tirosina nas plantas.
Potassium phosphite does not protect maize plants against the phytotoxic effects of glyphosate
Keywords: Zea mays; shikimic acid; quinic acid; aromatic amino acids; Zea mays; ácido chiquímico; ácido quínico; aminoácidos aromáticos